UMP spreads wings to Sarajevo - UMP, PNC
Universiti Malaysia Pahang (UMP) has spread its wings to Sarajevo when it signed a Memorandum of Understanding (MoU) in the fields of academic development as well as research and development with the University of Sarajevo last October 20.